2019
DOI: 10.1016/j.jretconser.2017.08.021
|View full text |Cite
|
Sign up to set email alerts
|

How do materialists choose prominent brands in emerging markets?

Abstract: Materialism is a worldwide phenomenon. However, our knowledge about the effect of materialism on consumer brand choice is limited. This study unlocks the path from materialism to brand prominence focusing on fashion, quality, and price consciousness. Our findings within the Chinese context show that the paths from materialism to fashion, quality, and price consciousness are positive. Further, we found that the paths from fashion and quality conscious to brand prominence are positive, while the path from price … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Past research found that price consciousness is a crucial factor that influences consumers' behavioural intentions (Campbell et al, 2014;Chung and Petrick, 2012;Lindblom et al, 2018;Siahtiri and Lee, 2019;Thanasuta, 2015). However, the vital role of attachment in mediating the relationship between price consciousness and guest booking intention in Airbnb service accommodation is yet to be examined.…”
Section: Mediating Role Of Attachment To Airbnbmentioning
confidence: 99%
“…Past research found that price consciousness is a crucial factor that influences consumers' behavioural intentions (Campbell et al, 2014;Chung and Petrick, 2012;Lindblom et al, 2018;Siahtiri and Lee, 2019;Thanasuta, 2015). However, the vital role of attachment in mediating the relationship between price consciousness and guest booking intention in Airbnb service accommodation is yet to be examined.…”
Section: Mediating Role Of Attachment To Airbnbmentioning
confidence: 99%
“…Rising consumerism in India has led to the increased popularity of luxury brands. In developed countries, people care less about others’ opinions and consume luxury products for personal gratification (Cheah et al , 2015) and luxury consumption is defined by group identity and affluence (Heany et al , 2005; Shukla and Purani, 2012; Pino et al , 2019; Siahtiri and Lee, 2019). In EMs such as India, luxury brands are viewed as products that elevate one’s social position and distinguish them from the crowd (Ramchandani and Coste-Manière, 2012).…”
Section: Review Of Literaturementioning
confidence: 99%
“…developed vs emerging markets) remain scarce. Researchers have examined the role branding plays in emerging markets, country-of-origin effect on adoption of global brands in emerging markets, and positive consumer dispositions toward domestic products (Kinra, 2006; Omar and Ensor, 2011; Siahtiri and Lee, 2017). Responding to recent calls for research (Riefler and Diamantopoulos, 2009; Wang, He and Barnes, 2017), this study examines differences in consumer dispositions towards global brands from emerging and developed markets.…”
Section: Introductionmentioning
confidence: 99%